Does enforcement of the rules against foreign bribery discourage exports? A case of the OECD Anti-Bribery Convention - Michal Paulus; Jaromír Baxa; Eva Michalíková (Charles University in Prague, Institute of Economic Studies (IES), 2020)
Although the OECD Anti-Bribery Convention has been signed by dozens of countries, only some of them enforce the laws against foreign bribery. To estimate whether the enforcement deters exports, we use a microfounded gravity model of bilateral trade flows of 132 countries. Our results imply that enforcement of the rules decreases the export flows to countries with a higher corruption distance significantly, particularly in product categories characterized by differentiated goods. Moreover, the effects of the host-country corruption on exports of the nonenforcing countries are limited, and similar to the impact on the exports from countries that did not sign the Convention at all. Therefore, the main aim of the Convention to level the field in international trade has not been reached yet, even among the signatory countries.
Keywords: F13; F14; F53; 330; Corruption; International trade; Gravity model